Effects of zeolite-amended sandy soil on moisture, ash, and protein content of Swiss Chard - Sindesi, Olwetu Antonia; Ncube, Bongani; Lewu, Muinat Nike; Mulidzi, Azwimbavhi Reckson; Lewu, Francis Bayo (Indonesian Journal of Agricultural Research, 2025)
Soil degradation and water scarcity are major challenges affecting crop productivity in sandy soils. Zeolite, a naturally occurring aluminosilicate mineral, has been explored as a soil amendment to improve soil properties and enhance plant growth for various crops. However, limited information on the influence of zeolite soil amendment on Swiss chard nutritional content. A greenhouse pot experiment was conducted at the Agricultural Research Council, Infruitec-Nietvoorbij, Stellenbosch, South Africa from late autumn to late spring. The study accessed the effects of zeolite soil amendment on dry matter yield, moisture content, crude ash, and crude protein of Swiss Chard (Beta vulgaris var. cicla cv. Ford Hook Giant) over five harvests. The experiment was laid out in a completely randomised block design with four treatments 0; 10; 20 and 30% zeolite application to sandy soil, all at 12 kg sandy soil or sandy soil and zeolite mixture. Data were analysed using analysis of variance (ANOVA), and treatment means were compared using Fisher’s least significant difference test at a 5% probability level. The results of this study show that zeolite through its porous nature, high cation exchange capacity and alkalinity may be used to improve water availability to plants (moisture content) while at the same time improving dry matter yields and mineral accumulation (crude ash content). However, zeolite did not improve the crude protein contents of Swiss chard, which is a function of nitrogen assimilation. Nevertheless, 20–30% zeolite application levels can be used as an effective method to combat soil degradation and mitigate drought-related challenges. These rates improved dry matter yields, enhanced crop moisture content, and promoted crude ash and/or mineral accumulation in Swiss chard.